(untitled) (Damascus University Journal of agriculture sciences, 2026)
The research was carried out on a private farm on Ross hybrid, during the period from 4/1/2021 - 5/15/2021 on 375 birds. It aims to determine the effect of the difference in the protein percentage in different age stages of broiler fattening mixtures on some productive indicators. The birds were divided into five groups. Nutrition (control + 4 experimental groups) in each group 75 birds, each of which was distributed to three replicates; in each replicate there were (25) birds. The chicks were fed according to the freely three-stage system (Ad Libitum) on fodder mixtures rich in local fodder. The first stage was (1-14 days), the second stage was (15-35 days) and the third stage was (36-42 days). Each stage included five mixtures of different fodders in their protein content. The results have showed that: - The increase in the percentage of crude protein in the fodder mixtures provided to birds (the second and third groups) led to: a significant increase (P? 0.05) compared to the control group for the following indicators: average live weight, daily growth rate, relative growth rate, protein consumption to obtain 1 / kg live weight and metabolic rate. The feed conversion factor was lower by 383 / grams (P? 0.05) at the age of 14 / days and by 227 / grams at the age of 15-35 / days (P ? 0.05). However, the increase in the proportion of protein in the third age stage from (36-42) days led to an increase in the feed conversion factor by an amount ranging from 672 to 1220 / grams, in comparison with the control group (P? 0.05), and an increase in the rate of feed consumption (P? 0.05). The mortality rate was within the normal limits (P>0.05). Reducing the percentage of crude protein in the feed mixtures provided to birds (the fourth and fifth groups) resulted in a decrease in: average body weight (P? 0.05), daily growth rate (P? 0.05), growth rate (P? 0.05).), feed consumption rate (P? 0.05), cumulative weight gain (P? 0.05), decrease in protein consumption rate to obtain 1 / kg live weight (P? 0.05), and decrease in metabolic rate (P? 0.05). Feed conversion coefficient was lower by 25 / grams at the age of 14 / days compared to the control, and by 98 / grams at the age of 15-35 / days (P? 0.05) and by 223 / grams in the third age stage (36-42) days. Mortality rate was higher (P> 0.05). Keywords: chicken broilers, productivity indicators